Pengaruh Disiplin Kerja Dan Kepemimpinan Terhadap Kinerja ASN Bawaslu Provinsi Kalimantan Timur - Perdata, Raden Dion Erik; Sukristyanto, Agus; Indartuti, Endang (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Bawaslu of East Kalimantan Province is the institution responsible for overseeing the implementation of elections within the region. In carrying out this mandate, the support of human resources with adequate discipline, leadership, and performance is essential. This study aims to identify and analyze the influence of work discipline and leadership on the performance of civil servants at Bawaslu East Kalimantan Province. This research uses a quantitative approach with a survey method, in which data were collected from a number of respondents through a questionnaire instrument. The study population includes all civil servants working at Bawaslu East Kalimantan and stakeholders who receive services from the institution. The sample consisted of 96 individuals, selected using purposive sampling and considered to represent the population proportionally. The research variables include work discipline (X1) and leadership (X2) as independent variables, and performance (Y) as the dependent variable. The results show that work discipline has a positive and significant effect on performance, with a regression coefficient (β) of 0.310 and a significance level of 0.000. Likewise, leadership also has a positive and significant effect on performance, with a regression coefficient (β) of 0.310 and a significance level of 0.000.